Evalualian ali 5 primitive races ai calton !or antibiasis efleci an canon iea!wanri. - Penna, Julio C.V.; Fallieri, Joel; Ferreira, Levi (Pesquisa Agropecuaria Brasileira, 2013)
Fifleen prirnflive races cl cetton (T' race stocks) were evaluated under contrciled condilions, for antbiosis effect on Iarvae and pupae ofcotton Iealwom,s, in 1983,0 Centro Regional de Pesquisa do Triângulo e Alto Paranafoa (CRTF-EPAMIG), MG, Brazil. Larvae received a leal diet ol lhe genmplasms studied, during twelve days, and lhen were weighed. Races T-295, T-284 and T'254 were responsible ler Uie attainnient ol toe lightest larvae, respealvelly 0.066, 0.078 and 0.100 g. Races T-169, T-133, T-25 and T-119 produced the lightest pupae, respectivelly 0,184, 0.168, 0.196 and 0.198 g. Correlation between larva and popa weigtu was notsigriflcanl,